2000
DOI: 10.1163/22134379-90003838
|View full text |Cite
|
Sign up to set email alerts
|

Shared responsibility; Some aspects of gender and authority in Makassar society

Abstract: A long time ago, a bamboo cane came floating down the Jeneberang river from Mount Bawakaraeng. A beautiful woman emerged from the bamboo. She went ashore near our village and sat down on a big red stone. There some people from the village found her and asked her to follow them to their houses. There was no ruler in the village at that time, and continuous quarreling and disputing prevailed among the inhabitants. They called the woman Bombong Koasa and asked her to become their ruler, since she was a divine bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…This study shows the Soroakan adoption of Bugis adat in their daily activities and how the mining company has impacted on the social relationship of the surrounding community as the result of the development of political economy in Soroako, including their marital relation. Röttger-Rössler's (2000) examines some aspects of gender and authority in Makassar society. She found that right, obligations, and the scope of authority are not dominated by men, but must be evenly distributed between men and women, and that responsibility is shared between the sexes in this society.…”
Section: Ethnograhic Research On Marriage In South Sulawesimentioning
confidence: 99%
“…This study shows the Soroakan adoption of Bugis adat in their daily activities and how the mining company has impacted on the social relationship of the surrounding community as the result of the development of political economy in Soroako, including their marital relation. Röttger-Rössler's (2000) examines some aspects of gender and authority in Makassar society. She found that right, obligations, and the scope of authority are not dominated by men, but must be evenly distributed between men and women, and that responsibility is shared between the sexes in this society.…”
Section: Ethnograhic Research On Marriage In South Sulawesimentioning
confidence: 99%
“…For women in the Makassar area of South Sulawesi, authority in the political arena is reflected in the institution of female ada ' (ada' bainé), where women act as partners to male members in the traditional governmental council (Röttger-Rössler, 2000). Makassar women may also play the role of mediator between general society and local leaders.…”
Section: Introductionmentioning
confidence: 99%
“…Makassar women may also play the role of mediator between general society and local leaders. Another factor, which might suggest the significance of Makassar women's role in the political arena, is that a husband might obtain a high-standing social position, such as a customary leader, based on the status of his wife (Röttger-Rössler, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations